A SOCIO-PRAGMATICS ANALYSIS OF OFFER ACTS IN MOVIE MANUSCRIPT - WIDOWATI , ITA (2007)
This research is aimed at clarifying the form of offer acts, clarifying the reasons in employing offer acts, and describing the politeness strategy used in offer acts. In collecting the data, the writer uses document method. The data are in the form of words, phrases and sentences which are used to propose offer acts. To clarify the form, the writer refers to the linguistics form theory. In clarifying the reasons of offer acts, the writer employs SPEAKING Hymes Formula. The writer applies Brown and Levinson Politeness theory in describing the politeness strategies used in offer acts. Having analyzed the data, the writer finds that the forms of offer acts are imperative, interrogative and declarative. Related to the reasons, the writer gets five kinds of reasons namely; showing solidarity, showing respect, showing appreciation, showing intimacy, and showing apology. The politeness strategies uses in offer acts are bald on record, positive politeness and negative politeness strategy. The use of each form is closely related with the strategy used in delivering an offer.